Isocitrate dehydrogenase mutations: a challenge to traditional views on the genesis and malignant progression of gliomas - Weller, Michael; Wick, Wolfgang; Deimling, Andreas von (Glia, 2011)
Isocitrate dehydrogenases (IDHs) convert isocitrate to α-ketoglutarate by oxidative decarboxylation and are thereby involved in multiple metabolic processes. Mutations in the genes encoding IDH1 and IDH2 were first reported in human gliomas in 2008 and later on also identified in a minority of patients with acute myeloid leukemia. The mutations universally affect codons 132 in IDH1 and 172 in IDH2 and result in decreased enzymatic activity. The oncogenic pathway triggered by IDH mutations may involve the activation of hypoxia-inducible factor pathway as well as the acquisition of a novel (gain of enzymatic) function consuming NADPH and generating α-hydroxyglutarate. Most intriguingly, IDH mutations are observed in ∼70-80% of grade II/III gliomas and the majority of secondary glioblastomas, but only 10% of primary glioblastomas, suggesting a different cellular origin of the gliomas, which had previously been viewed as a multistep process of malignant progression. Understanding the oncogenic pathway mediated by mutant IDH might result in the development of novel, tailored pharmacological therapies for human glioma patients. © 2011 Wiley-Liss, Inc.